Monetary policy in Argentina: From the inflation of the 1970s to the default of the new millennium - Vittoria Ferrandino; Valentina Sgro (The European Association for Banking and Financial History (EABH), 2015)
Since the end of World War II, Argentina has been through an uninterrupted series of financial/fiscal and monetary crises that have gradually eroded the credibilityof the economic institutions of the country. In the period from 1970 to 1990 alone, the Argentine economy experienced seven currency crises and three banking crises. The main objective of this contribution is to investigate the reasons for economic policy choices that, since the military dictatorship of Colonel Perón, have led the country to default, causing unemployment, runs on banks and popular uprisings.
Keywords: N16; N26; N46; 330; monetary policy; financial crisis; Argentina